Pengelolaan Wilayah Pesisir dan Pulau-Pulau Kecil di Kabupaten Lingga Berdasakan Undang Undang Nomor 1 Tahun 2014 Tentang Perubahan Atas Undang Undang Nomor 27 Tahun 2007 - Suparto Suparto; Muhammad Faizal Pahlevi (Jurnal Selat, 2021)
Lingga Regency has an area of ​​45,508.66 km2 with a land area of ​​2,235.51 km2 and an ocean 43,273.15 km2, with 531 large and small islands. There are still many small islands that have not been exploited for their natural resources and marine resources. Regarding the management of coastal areas, currently it has been regulated in Law no. 27 of 2007 in conjunction with Law no. 1 of 2014 concerning the Management of Coastal Areas and Small Islands (UU PWP3K). The formulation of the problem is how to implement the PWP3K Law and the obstacles faced by the Lingga Regency government. Based on the research, the results show that the implementation of the PWP3K Law has not run properly, because there is no regional regulation (Perda) on the Zoning Plan for Coastal Areas and Small Islands (RZWP3K) by the Riau Islands Province which is the legal umbrella for the Lingga Regency Government in managing coastal areas and islands. small island. The Lingga Regency Government currently prioritizes agricultural/agro-industry development programs even though developments in the marine and fisheries sector should require more special attention because most of the people work as fishermen and the area itself is included in the category of Coastal and Small Island areas. Another obstacle faced by the Lingga Regency Government is the limitation of authority between the Provincial Government and Regency/City Governments in Law no. 23 of 2014 concerning Regional Government in terms of marine, coastal and small island management.